Z-source reversing voltage multilevel inverter for photovoltaic applications with inherent voltage balancing - Ehsan Najafi; Amir Hosein Rashidi; Seyed Mohammad Dehghan (Institute of Advanced Engineering and Science, 2022)
Photovoltaic (PV) inverters have been widely used in solar energy to change the direct current (DC) voltage of PV panels to the grid alternating current (AC) voltage. They are comprised of DC-DC section for maximum power point tracking (MPPT) and DC-AC part to provide required output AC voltage. This paper provides a unique configuration that integrates both sections in one part. A Z-source multilevel inverter is proposed based on Z-source networks and reversing voltage (RV) multilevel inverter. The Z-source network can be used to increase the level of the input voltages and MPPT as well. In addition, the prop used topology uses multilevel topology to accommodate more DC inputs and benefit from features of multilevel level inverters in AC output. Moreover, using Z-source network can minimize equated monthly installment (EMI) due to the lower stress on the semiconductor switches. Finally, a seven level topology is designed and simulated to show the performance of proposed topology.